Using Kaplan Meier and cox regression in survival analysis : An example / Teoh Sian Hoon - Teoh, Sian Hoon (Universiti Teknologi MARA Pulau Pinang, 2008)
The Kaplan Meier procedure is used to analyze data based on the survival time. This article provides an example on how to use Kaplan Meier and Cox regression with three objectives. The objectives are finding the percentage of survival at any time of interest, comparing the survival time of two studied groups and examining the effect of continuous covariates with the relationship between an event and possible explanatory variables. The example is discussed based on the breast cancer survival dataset from Statistical Package for the Social Sciences (SPSS).